Evaluation of dry needling and 0.5% lidocaine injection therapies in myofascial pain trigger points in masticatory muscles - Silva,Renato Oliveira Ferreira da (2012)
OBJECTIVE: The purpose of this study was to compare the effectiveness of trigger points injections using lidocaine 0.5% and dry needling without any kind of home-based rehabilitation program. METHODS: Sixteen patients with myofascial pain and trigger points in masticatory muscles were randomly assigned to two groups and received only one application session. The pressure pain threshold (PPT) was recorded before and after the injection: Ten minutes, 24 hours later, 7, 15, 21 and 30 days after the treatment. Visual analogue scale (VAS) was used to in all evaluation periods. RESULTS: There were no difference between groups for PPT, but for all groups the PPT during the time significantly increased when compared the before treatment. VAS showed differences between groups and during the time. The 0.5% lidocaine had the lowest VAS values when compared to dry needling, but at 30 days there were no differences among them. CONCLUSIONS: Despite the differences in VAS and considering there were no differences in PPT increases, we concluded that, in this study, both groups were able to disrupt the mechanisms of trigger point and relieve the myofascial pain symptoms.